Kebijakan Dividen Ditinjau Menggunakan Profitabilitas, Leverage, Set Kesempatan Investasi dan Arus Kas Bebas - Jasmine Jasmine; Nera Marinda Machdar (Pusat Riset dan Inovasi Nasional, 2025)
The development of the financial sector in Indonesia encourages companies to enhance their value through optimal dividend policies. This study aims to analyze the influence of profitability, leverage, investment opportunity set, and free cash flow on dividend policy among banking sector companies listed on the Indonesia Stock Exchange. Utilizing a literature review method, this research examines 40 articles and journals published between 2019 and 2024 to explore the relationships between these variables. Based on agency theory and signaling theory, dividend policy is influenced by internal factors such as profitability and free cash flow, as well as strategic decisions related to leverage and investment opportunities. The findings indicate that each variable affects dividend policy differently, depending on the company’s circumstances and management strategies. These insights are expected to serve as a reference for future studies and as guidance for corporate management in effectively managing dividend policies to attract investors and enhance company value.